Pengendalian Pencemaran Lingkungan Atas Keberadaan Tambak Udang Ilegal di Batang Anai Kabupaten Padang Pariaman Sebagai Upaya Perlindungan Hukum Terhadap Kesehatan Masyarakat - Siska Elvandari; Ansiha Nur; Budhi Primasari (UNES Law Review, 2023)
The growth of illegal shrimp ponds in Batang Anai, Padang Pariaman Regency has been very widespread recently. This is because the advantages of shrimp cultivation include fast growth, high survival rate, high shrimp appetite, greater resistance to disease attacks and relatively short rearing time, namely 90-100 days per cycle. As shrimp cultivation develops in this area, environmental pollution problems arise. Of course, this is contrary to Law number 36 of 2009 concerning Health, Article 4 and Article 6 states that everyone has the right to health and everyone has the right to a healthy environment for achieving a level of health. Based on preliminary interviews with the community around the shrimp ponds, it was stated that the existence of illegal shrimp ponds does not take into account the impact on the environment, and even disturbs the community. Meanwhile, there is no action by the district or local government to control or manage the impacts, so various efforts are needed to restore optimal health status for the surrounding community.